The Impact of the Application of Lexical Approach on Developing Students’ Writing Skills at a University Level - Abdulqader, Hassan Basil; Murad, Ivan Hasan; Abdulghani, Marwah Ihsan (European Scientific Journal, ESJ, 2017)
This paper aims at investigating experimentally the effect of applying the Lexical Approach (henceforth LA) on the achievement of third-year University students of English in the cause and effect essay writing. It examines theoretically and practically the LA and the notion of lexical units in English along with explaining some other relevant points. The two groups, pre-test and post-test experimental design were adopted to ensure groupmatching control over the intervening variables. After six weeks of instruction based on the LA, the results revealed that the experimental group had statistically significant gain scores between their pretests and posttests in the essay-writing test. The control group, however, did not have statistically significant gain scores on the dependent measure. The LA was beneficial to the third-year students. Consequently, the major findings validated the hypothesis of the study. In view of the findings obtained, application of the LA has been recommended and a number of pedagogical implications have been presented.